Letter: colorectal cancer surveillance in inflammatory bowel disease—a call for systematic reform. Issue 8 (21st March 2021) - Prentice, Ralley E.; Hollingsworth, Laura; Middleton, Christopher; Wilson, Jarrad
Abstract : LINKED CONTENT This article is linked to Gordon et al paper. To view this article, visit https://doi.org/10.1111/apt.16155